The Amish quiltmaker's unattached neighbor - Beckstrand, Jennifer (Beckstrand, Jennifer. Amish quiltmaker., 2024)
"At thirty-two, Ada Yoder is resigned to caring for her three sisters, her ever-impractical father, and their prosperous, but demanding, farm. The last kind of trouble she needs is Enos Hoover claiming that six acres of their land actually belongs to him--and taking steps to prove it. But Ada soon finds that battling Enos' clever strategies is delightfully intriguing--and lighting an impossible spark... Enos is determined to make his mater proud by turning difficult acreage into a successful farm. Legally, he is in the right to reclaim the land from the Yoders. But Ada's hard-working stubbornness and refreshing honesty are proving to be more of an irresistible challenge than an obstacle. Now, can Enos and Ada find enough faith and understanding to reconcile family, duty, and love--and stake their claim on a forever happiness together?"--